Communicating Information on Eruptions and Their Impacts from the Earliest Times Until the Late Twentieth Century - Rui Coutinho; Angus M. Duncan; Nicolau Wallenstein; Stefano Branca; David K. Chester (2017)
Volcanoes hold a fascination for human beings and, before they were recorded by literate observers, eruptions were portrayed in art, were recalled in legend and became incorporated into religious practices: being viewed as agents of punishment, bounty or intimidation depending upon their state of activity and the culture involved. In the Middle East the earliest record dates from the third millennium BCE and knowledge of volcanoes increased progressively over time. In the first century CE written records noted nine volcanoes in the Mediterranean region plus Mount Cameroon in West Africa, yet by 1380 AD the record only totalled 48, with volcanoes in Japan, Indonesia and Iceland being added. After this the list of continued to increase, but important regions such as New Zealand and Hawaii were only added during the last 200 years. Only from 1900 did the rate of growth decline significantly, but it is sobering to recall that in the twentieth century major eruptions have occurred from volcanoes that were considered inactive or extinct, examples including: Mount Lamington—Papua New Guinea, 1951; Mount Arenal—Costa Rica, 1968 and Nyos—Cameroon, 1986. Although there were instances where the human impact of historical eruptions were studied in detail, with examples including the 1883 eruption of Krakatau and 1943–1952 eruption of Paricutin, these were exceptions and before 1980 there was a significant knowledge gap about both the short and long-term effects of major eruptions on societies. Following a global review, this chapter provides a discussion of the ways in which information has been collected, compiled and disseminated from the earliest times until the 1980s in two case study areas: the Azores Islands (Portugal) and southern Italy. In Italy information on eruptions stretches back to prehistoric times and has become progressively better known over more than 2,000 years, yet even here there remain significant gaps in the record even for events that took place between 1900 and 1990. In contrast, located in the ...